Limitations in the Use of Formal Indonesian and Socio-Cultural Influences on Academic Participation: A Case Study of Eastern Indonesian Students - Deana Indah Haimima; Agung Hastomo; Muhammad Fikruzzaman Makarim; Rooselina Ayu Setyaningrum; Muammar Muammar (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2026)
This study examines barriers to formal Indonesian language use and sociocultural influences on academic participation among Eastern Indonesian students in the Elementary School Teacher Education Program at Sanata Dharma University. A qualitative case study with purposive sampling involved five Eastern Indonesian students and one lecturer through in-depth interviews, classroom observations, and academic document analysis, subsequently analyzed thematically. Three primary barriers were identified: linguistic interference from regional accents undermining self-confidence, limited formal vocabulary hindering academic expression, and social isolation stemming from stereotyping. Linguistic and psychosocial barriers mutually reinforced one another, creating a cycle that impeded academic participation. Grounded in linguistic insecurity theory, BICS/CALP, and sociocultural theory, students developed cognitive, social-collaborative, and metacognitive adaptation strategies, yet continued requiring systematic institutional support. Integrating formal Indonesian language training programs, establishing inclusive academic environments, and enhancing lecturer sensitivity toward linguistic diversity are critical to ensuring equitable access and academic success for students from diverse linguistic backgrounds in Indonesian higher education.